The Effect of Cash Holdings And Solvency on Profitability: Multinational Companies Coal Production Subindustry Listed (IDX) - Syahla Nur Fikriyyah; Djalalludin Akbar; Perwito Perwito (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Cash management in multinational companies is very important in maintaining liquidity and optimizing profits. Currency differences are one of the factors that encourage companies to implement quality cash management in order to avoid losses caused by currency fluctuations. The purpose of this study is to examine whether cash holdings and solvency can affect the profitability of multinational companies in the coal production sub-industry listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. The results of the study indicate that cash holdings affect profitability, while solvency does not affect profitability. Overall, the dependent variables simultaneously affect the independent variables.